Influence of Long-Period-Stacking Ordered Structure on the Damping Capacities and Mechanical Properties of Mg-Zn-Y-Mn As-Cast Alloys - Ruopeng Lu (Materials, 2020)
Magnesium alloys are concerned for its mechanical properties and high damping performance. The influence of Mn toward the internal organization morphology of long-period stacking ordered (LPSO) second phase and the consistent damping performance in Mg-4.9Zn-8.9Y-xMn have been studies in this work. It has shown that the addition of Mn tends to diffuse to the LPSO interface and causes the LPSO phase to expand in the arc direction. The circular structure of LPSO can optimize the damping property of the alloy better than the structure with strong orientation, especially at the strain of 10−3 and 250 °C. With more additions of Mn, damping would have a reduction due to the dispersed fine LPSO phases and α-Mn particles. When the Mn content is higher than 1.02%, the grain is refined, and mechanical properties have been significantly improved. Mg-4.9%Zn-8.9%Y-1.33%Mn shows the best mechanical property.